Jawetz, Melnick, & Adelberg's Medical Microbiology - Brooks, Geo; Butel, Janet S. ;Morse, Stephen A. (New York : Lange Medical Books/McGraw-Hill, Medical Pub. Division, 2001)
This work focuses on the ever-increasing knowledge about the relationship of pathogenic microorganisms to human disease and the application of that knowledge to the diagnosis and treatment of these illnesses. It covers topics such as the basic and clinical aspects of microbiology and virology.
Section I. Fundamentals of microbiology -- II. Immunology -- III. Bacteriology -- IV. Virology -- V. Mycology -- VI. Parasitology -- VII. Diagnostic medical microbiology & clinical correlation.
Includes bibliographical references and index.
Keywords: MEDICAL MICROBIOLOGY